Pengaruh Litererasi Keuangan, Akses Pembiayaan dan Perencanaan Keuangan Terhadap Keberlanjutan Usaha Mikro di Night Market Pasar Besar Kota Malang. - Ramadhan, Fathur; Susyanti, Jeni; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyse and describe the effect of Financial Literacy, Access to financing and Financial Planning on Micro Business Sustainability in the Night Market Pasar Besar Malang City. The population used in this study were micro business owners in the night market Pasar Besar Malang City. The sample in the study using the Slovin formula obtained 93 respondents. This study analyses data using the Statistical Package for the Social Science (SPSS) Version 30.00 tool. The dependent variable used in this study is Business Sustainability, Financial Literacy, access to financing and financial planning as independent variables. The results of this study indicate that Financial literacy has no significant effect on business sustainability,  Access to financing has a negative Significant effect on business sustainability, Financial planning has no significant effect on business sustainability. Keywords: Business Sustainability, Financial Literacy, Access to Financing, Financial Planning